Play therapy theory and practice : comparing theories and techniques - Braverman, Lisa D.; O'Connor, Kevin J. (John Wiley & Sons, 2009)
A guide to the ten major approaches to play therapy. It covers bipolar and ADHD diagnosis and the use of psychotropic medications. It also covers the use of major models of play therapy. It is suitable for therapists looking to sharpen their skills and students seeking initial training